2005
DOI: 10.1128/iai.73.10.6868-6876.2005
|View full text |Cite
|
Sign up to set email alerts
|

Poly- N -Acetylglucosamine Production in Staphylococcus aureus Is Essential for Virulence in Murine Models of Systemic Infection

Abstract: The contribution of the Staphylococcus aureus surface polysaccharide poly-N-acetylglucosamine (PNAG) to virulence was evaluated in three mouse models of systemic infection: bacteremia, renal abscess formation, and lethality following high-dose intraperitoneal (i.p.) infection. Deletion of the intercellular adhesin (ica) locus that encodes the biosynthetic enzymes for PNAG production in S. aureus strains Mn8, Newman, and NCTC 10833 resulted in mutant strains with significantly reduced abilities to maintain bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 78 publications
(103 reference statements)
5
139
1
3
Order By: Relevance
“…24 The S. aureus Newman, S. epidermidis RP62A and the E. coli XL 1 Blue strains are producers of PNAG and the WGA assay is well applicable to them. [25][26][27] The S. epidermidis 12228 is negative for the ica locus and it is often referred to as a non-biofilm or weak biofilm producer. 27,28 In the absence of PNAG, the WGA probe is probably unable to bind to the matrix of the biofilms formed by the S. epidermidis 12228 and when using this strain, highly diverting signals, including negative Z 0 -values were in fact registered, thus impeding the application of the WGA assay.…”
Section: Resultsmentioning
confidence: 99%
“…24 The S. aureus Newman, S. epidermidis RP62A and the E. coli XL 1 Blue strains are producers of PNAG and the WGA assay is well applicable to them. [25][26][27] The S. epidermidis 12228 is negative for the ica locus and it is often referred to as a non-biofilm or weak biofilm producer. 27,28 In the absence of PNAG, the WGA probe is probably unable to bind to the matrix of the biofilms formed by the S. epidermidis 12228 and when using this strain, highly diverting signals, including negative Z 0 -values were in fact registered, thus impeding the application of the WGA assay.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the expression of PNAG, we used several strains of staphylococci, including PNAG-positive S. aureus MN8 (15) and S. epidermidis M187 (39) and PNAGnegative S. aureus MN8⌬ica (8). E. coli strains used included CFT073, a urinary tract isolate previously shown to contain the pga locus (18), and 30 clinical isolates of E. coli collected over different periods of time and also geographically distant.…”
Section: Methodsmentioning
confidence: 99%
“…In both staphylococci and E. coli, the PNAG polymer promotes biofilm formation and is cell surface-associated (5,6,18). In staphylococci, PNAG has been found to be a virulence factor (8,(31)(32)(33) and target for protective Ab (14)(15)(16). In this work, we report that a high percentage of E. coli UTI and neonatal bacteremia isolates contain the icahomologous pga genetic locus and synthesize PNAG that is immunologically cross-reactive with PNAG isolated from S. aureus, and the production of PNAG by E. coli allows opsonically active antibodies raised to the S. aureus dPNAG antigen to mediate in vitro killing of these organisms.…”
Section: E Coli Is An Important Cause Of Gastrointestinal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…PNAG, which is synthesized by enzymes encoded in intercellular adhesin (ica) locus, contributes to bioilm formation, colonization in host tissue, and immune evasion [51,52]. Recent work showed that deacetylation of PNAG (dPNAG) by surface protein, IcaB, is a critical step for PNAG association to cell wall and plays key roles in colonization and resistance to host immune defense [53].…”
Section: Capsular Glycopolymer As Antibody Targetmentioning
confidence: 99%